2007
DOI: 10.1086/519499
|View full text |Cite
|
Sign up to set email alerts
|

The Biasing Health Halos of Fast-Food Restaurant Health Claims: Lower Calorie Estimates and Higher Side-Dish Consumption Intentions

Abstract: Why is America a land of low-calorie food claims yet high-calorie food intake? Four studies show that people are more likely to underestimate the caloric content of main dishes and to choose higher-calorie side dishes, drinks, or desserts when fast-food restaurants claim to be healthy (e.g., Subway) compared to when they do not (e.g., McDonald's). We also find that the effect of these health halos can be eliminated by simply asking people to consider whether the opposite of such health claims may be true. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
502
5
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(552 citation statements)
references
References 51 publications
25
502
5
9
Order By: Relevance
“…The findings reported in the present study confirmed earlier research that colour is indeed influential in forming consumer impressions of healthiness (10) ; however, it has contributed by demonstrating that this effect is subject to the moderating influence of product category heuristic halos (3,33) . Results show that perceived healthiness of a product has biasing influence on what role colour coding can play in healthfulness evaluations, thus importantly qualifying earlier work on colour labels' efficacy in healthful food selection (11,12) .…”
Section: Discussionsupporting
confidence: 90%
“…The findings reported in the present study confirmed earlier research that colour is indeed influential in forming consumer impressions of healthiness (10) ; however, it has contributed by demonstrating that this effect is subject to the moderating influence of product category heuristic halos (3,33) . Results show that perceived healthiness of a product has biasing influence on what role colour coding can play in healthfulness evaluations, thus importantly qualifying earlier work on colour labels' efficacy in healthful food selection (11,12) .…”
Section: Discussionsupporting
confidence: 90%
“…Also consistent with our hypothesis, previous research demonstrates that healthy eating can rebound, for example, when individuals increased consumption of (both healthy and unhealthy) food after eating food that was presented as low-fat or as coming from a small-quantity package (Chandon and Wansink 2007;Coelho Do Vale, Pieters, and Zeelenberg 2008;Raghunathan et al 2006). However, if satisfying the health goal makes people feel hungry, we expect that they should be hungrier than when they do not eat anything.…”
Section: The Impact Of External Controlssupporting
confidence: 88%
“…Previous research attests that people make logical inferences that low-calorie food is less fulfilling than high-calorie food and thus overcompensate by eating too much of both healthy and unhealthy food. For example, participants who sampled foods labeled as "low fat" consumed more food, regardless of the food's healthful properties, than when they sampled foods labeled as "regular" (Chandon and Wansink 2007;Wansink and Chandon 2006). Whereas logical inferences of this type account for differences in consumption between healthy and unhealthy foods, they are not the underlying mechanism for the effect of healthy food on experienced hunger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helping parents to understand how common heuristics affect their own food choices is a possibility, and consumer research offers many insights here. For example, Chandon and Wansink (2007) found that adult consumers underestimate calories in a restaurant with a health positioning (Subway), and suggest educational interventions to combat such tendencies. These could be used by parents to modify their own behavior, and to educate their children when eating out.…”
Section: Parents' Knowledge and Beliefs About Healthy Householdsmentioning
confidence: 99%